Pneumocystis Pneumonia in Rheumatic Diseases: Prevention Issues - G. I. Gridneva; B. S. Belov; E. S. Aronova (Антибиотики и Химиотерапия, 2022)
The incidence of pneumocystis pneumonia (PCP) in patients with rheumatic diseases (RD) continues to increase. This is facilitated by the increasing use of genetically engineered biological agents in addition to the use of cytostatics and glucocorticoids. Mortality due to PCP among patients with RD is extremely high, so the issues of its prevention are relevant. European and American scientists focus on the frequency of detection of PCP and the determination of the proportionality of certain risk factors, while the recommendations for prevention are formulated cautiously. Asian medical communities are unanimous in their opinion about the need to prevent PCP, only the dosage of drugs and the duration of the course of treatment are discussed.